MR imaging and CT perfusion findings of an extraventricular neurocytoma - (:unkn) unknown (My University, 2009)
We present imaging findings of a 45-year-old-male patient referred for increasing left hemiparesis during the last few days. CT and CT perfusion (CTP) revealed a mass lesion with reduced regional cerebral blood flow (rCBF) and regional cerebral blood volume (rCBV) with prolonged mean transit time (MTT), suggesting either irreversible infarction or a low grade tumor. MRI revealed a well defined cortically based homogenous nonenhancing tumoral mass. Surgical excision was performed and histology showed extraventricular neurocytoma (EVN), a low grade tumor composed of synaptophysin positive and glial fibrillary acidic protein (GFAP) negative neuron cells. © 2008 Elsevier Ireland Ltd. All rights reserved.
Keywords: CT perfusion; Extraventricular neurocytoma; Low grade tumor; MRI